Processing of hippocampal network activity in the receiver network of the medial entorhinal cortex layer V - Rozov, Andrei; Rannap, Märt; Lorenz, Franziska; Nasretdinov, Azat; Draguhn, Andreas; Egorov, Alexei (The journal of neuroscience, 2020)
The interplay between hippocampus and medial entorhinal cortex (mEC) is of key importance for forming spatial representations. Within the hippocampal-entorhinal loop, the hippocampus receives context-specific signals from layers II/III of the mEC and feeds memory-associated activity back into layer V (LV). The processing of this output signal within the mEC, however, is largely unknown. We characterized the activation of the receiving mEC network by evoked and naturally occurring output patterns in mouse hippocampal-entorhinal cortex slices. Both types of glutamatergic neurons (mEC LVa and LVb) as well as fast-spiking inhibitory interneurons receive direct excitatory input from the intermediate/ventral hippocampus. Connections between the two types of excitatory neurons are sparse, and local processing of hippocampal output signals within mEC LV is asymmetric, favoring excitation of far projecting LVa neurons over locally projecting LVb neurons. These findings suggest a new role for mEC LV as a bifurcation gate for feedforward (telencephalic) and feedback (entorhinal-hippocampal) signal propagation. - SIGNIFICANCE STATEMENT Patterned network activity in hippocampal networks plays a key role in the formation and consolidation of spatial memories. It is, however, largely unclear how information is transferred to the neocortex for long-term engrams. Here, we elucidate the propagation of network activity from the hippocampus to the medial entorhinal cortex. We show that patterned output from the hippocampus reaches both major cell types of deep entorhinal layers. These cells are, however, only weakly connected, giving rise to two parallel streams of activity for local and remote signal propagation, respectively. The relative weight of both pathways is regulated by local inhibitory interneurons. Our data reveal important insights into the hippocampal-neocortical dialogue, which is of key importance for memory consolidation in the mammalian brain.
Gesehen am 24.11.2020